Efektivitas Pelayanan Rumah Pangan Kita (RPK) di Perusahaan Umum Badan Urusan Logistik (Perum Bulog) Kantor Cabang Bukittinggi - Muhammad Ridha; Adil Mubarak (PUBLICNESS: Journal of Public Administration studies, 2022)
This study aims to determine the effectiveness of the Rumah Pangan Kita (RPK) service at the General Logistics Affairs Agency (Perum BULOG) Bukittinggi Branch Office. This research was carried out using a qualitative descriptive approach in which data collection was based on the factors that became the main supporters of the research object. In this study, the withdrawal of informants was based on a purposive sampling technique which was based on the main criteria, namely that they must be the people of the City of Bukittinggi. This data collection is done by means of interviews, observation, and documentation. Data analysis is done by collecting data, reducing data, presenting data, and drawing conclusions. Then the validity of this data was tested by triangulation of sources which was then analyzed. Based on the findings, it can be concluded that the Rumah Pangan Kita program carried out by Perum BULOG at the Bukittinggi Branch Office has been effectively carried out through the RPK companion application. The obstacles experienced by partners are delays in payments exceeding the compensation provided by Perum Bulog